Answers

2015-06-04T11:14:13+05:30
We know that acceleration =final velocity-initial velocity/time
  here,
 final velocity=6 m/s
initial velocity=0 m/s (as he was at rest)
time =3 sec
acceleration=6-0/3
               =6/3
               =2 m/s²
0
2015-06-04T11:36:12+05:30
Given that,
final velocity (v) = 6 m/s
initial velocity (u) = 0 m/s
time taken=  seconds.
now,
we know that acceleration (a) is the rate of change of velocity in unit tme.
therefore,
a=  (v-u)/ t
= (6-0) / 3
=6/ 3
= 2 m/s²

thank you.....
0